A novel technique for estimating component sizes in total knee arthroplasty. (April 2018) - Rehman, Haroon; MacDonald, David R.W.; Smith, Matthew; Zainudin, Syaza; Robertson, Graham; Mitchell, Martin
Abstract: Introduction: Intra-operative assessment of total knee arthroplasty (TKA) components is performed with manufacturer specific jigs. Pre-operative templating, patient specific knee cutting blocks and computer-assisted surgeries have also been used to improve alignment and sizing; although the literature shows marginal improvement in functional scores. We propose pre-operative shoe size as a simple measurement tool for estimating the component sizes required for TKA. We investigate the relationship between TKA implant sizes, height, body weight and shoe size. Methods: Retrospective single centre cohort study of all patients undergoing primary knee arthroplasty over a four-month period (August–November 2015) was conducted. Standard data items recorded during routine admission. The spearman's rank correlation was used to assess the relationship between variables. Results: One hundred and six patients were included in the final analysis. The mean age of the study group was 67.3 ± 10.1 years (Range 44–90.) There were 42 male patients and 64 female patients. Statistically significant correlations were observed between: Shoe size and femoral component (rho = 0.589, p < 0.05); shoe size and tibial component (rho = 0.718, p < 0.05); shoe size and height (rho = 0.692, p < 0.05); height and femoral component (rho = 0.626, p < 0.05); height and tibial component (rho = 0.674, p < 0.05). Conclusion: We have demonstrated positive correlation between shoe and TKR component sizes. This relationship allows surgeons to estimate prosthesis size in the pre-operative setting. Highlights: We propose shoe size as a tool for estimating component size for total knee arthroplasty. Both variables were recorded for 106 total knee arthroplasty patients. Spearman's rank correlation was used to assess their relationship. Significant correlation between shoe size and femoral component. Significant correlation between and shoe size and tibial component.